A value-based Aswaja curriculum approach to strengthen moderate Islamic character in higher education - Khalimatus Sadiyah; Ajat Sudrajat; Rukiyati Rukiyati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the weakening internalisation of Islamic values in Islamic higher education, focusing on Nahdlatul Ulama institutions where Ahlussunnah Wal-Jama’ah (Aswaja) serves as an ideological foundation for strengthening moderate Islamic character. Using a qualitative multiple case study at Wahid Hasyim University Semarang and Balekambang Polytechnic Jepara, data were collected through in-depth interviews, participatory observation, and analysis of curriculum and institutional policy documents. The findings reveal four key patterns: Aswaja values are more strongly embedded in formal religious activities than in academic learning; institutional policies lack measurable indicators for Aswaja-based character outcomes; campus leadership plays a decisive role in shaping Aswaja institutional culture; and students tend to perceive Aswaja as an institutional identity rather than an ethical framework guiding academic practice. These findings indicate a gap between the normative vision of Aswaja and its practical implementation, resulting in symbolic and fragmented internalisation. This study concludes that strengthening moderate Islamic character requires a systemic Aswaja value-based curriculum integrating conceptual, pedagogical, and institutional dimensions, positioning Aswaja as an epistemological framework rather than merely a cultural symbol.